2021
DOI: 10.1177/02692163211019897
|View full text |Cite
|
Sign up to set email alerts
|

Identification of palliative care needs among people with dementia and its association with acute hospital care and community service use at the end-of-life: A retrospective cohort study using linked primary, community and secondary care data

Abstract: Background: Hospital admissions among people dying with dementia are common. It is not known whether identification of palliative care needs could help prevent unnecessary admissions. Aim: To examine the proportion of people with dementia identified as having palliative care needs in their last year of life, and the association between identification of needs and primary, community and hospital services in the last 90 days. Design: Retrospective cohort study using Discover, an administrative and clinical datas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Leniz et al 1 found that for those diagnosed with dementia, one and three had palliative care needs and one and five had needs that happened before the last 90 days. It was also identified that for those who had palliative care needs before the last days of life, they were likely to engage with the healthcare system through primary care community or community palliative care domains and to have less multiple non-elective admissions to the hospital in the last days of life.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Leniz et al 1 found that for those diagnosed with dementia, one and three had palliative care needs and one and five had needs that happened before the last 90 days. It was also identified that for those who had palliative care needs before the last days of life, they were likely to engage with the healthcare system through primary care community or community palliative care domains and to have less multiple non-elective admissions to the hospital in the last days of life.…”
Section: Resultsmentioning
confidence: 99%
“…Leniz et al 1 support the current initiatives to improve identification of an access to palliative care. This study reinforces the need to bolster the workforce of palliative care healthcare professionals and work on healthcare and systems-wide approaches to identifying palliative care needs.The needs of dementia patients at the end of life showcases one example of how identification of palliative care needs provides for better patient outcomes and decreases the incidence of acute care utilisation, ultimately improving patient experience at end of life.…”
Section: Commentarymentioning
confidence: 96%
See 2 more Smart Citations
“…Routinely collected data can also be used to shed light on patients with other conditions than cancer. Both the study of Leniz et al 8 and the study of Miranda et al 9 looked at older people diagnosed with dementia, a rapidly expanding group of patients. Leniz et al found in their retrospective cohort study that only a fraction of them were formally identified as having palliative care needs, even less so prior to the very end of life.…”
Section: The Promise Of Big Data For Palliative and End-of-life Care Researchmentioning
confidence: 99%